2020
DOI: 10.1038/s41467-020-19706-9
|View full text |Cite
|
Sign up to set email alerts
|

Immune suppression in the early stage of COVID-19 disease

Abstract: The outbreak of COVID-19 has become a worldwide pandemic. The pathogenesis of this infectious disease and how it differs from other drivers of pneumonia is unclear. Here we analyze urine samples from COVID-19 infection cases, healthy donors and non-COVID-19 pneumonia cases using quantitative proteomics. The molecular changes suggest that immunosuppression and tight junction impairment occur in the early stage of COVID-19 infection. Further subgrouping of COVID-19 patients into moderate and severe types shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
158
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(181 citation statements)
references
References 30 publications
6
158
0
1
Order By: Relevance
“…The time between sample collection and clinical presentation varied among patients and among groups. Our findings may thus be biased, especially because of the known stage-dependent immune alterations of COVID-19 ( Mann et al., 2020 ; Tian et al., 2020 ). Finally, neurological signs and symptoms in Neuro-COVID might not only depend on the observed CSF changes, but also on systemic factors, such as oxygen or serum cytokine levels.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The time between sample collection and clinical presentation varied among patients and among groups. Our findings may thus be biased, especially because of the known stage-dependent immune alterations of COVID-19 ( Mann et al., 2020 ; Tian et al., 2020 ). Finally, neurological signs and symptoms in Neuro-COVID might not only depend on the observed CSF changes, but also on systemic factors, such as oxygen or serum cytokine levels.…”
Section: Discussionmentioning
confidence: 93%
“…Studies with longitudinal clinical follow-up will be required to address this question. Additionally, the effects of immune responses may be stage-specific in Neuro-COVID as observed in the multi-stage kinetics in pulmonary COVID-19 ( Mann et al., 2020 ; Tian et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The infection of SARS-CoV-2 and progression of COVID-19 exhibit a ''two-stage'' pattern. During the early stage, mild or asymptomatic COVID-19 patients undergo immunosuppression, which facilitates significant viral shedding and transmission (Tian et al, 2020). Because ORF9b has emerged as a potent IFN antagonist during the early stage of SARS-CoV-2 infection, it is convincible that SARS-CoV-2 uses the early protein ORF9b to mask the antiviral defense and inflammatory response in earlystage patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the dysregulation may cause the accumulation on DNA damage or on the protein levels accumulating errors in the downstream cascade of mechanisms [59]. The role of EEF2 in severe cases of COVID-19 has also been elucidated in [51]. Thus our study provides another evidence.…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, elderly accumulate inflammatory mediators in tissues (inflammageing process), that may occur by the accumulation of DNA lesions that in turn, trigger the increased production of inflammatory mediators [50]. In parallel, the link between COVID-19 and the suppression of the immune system has been observed in [51]. Authors found that many proteins related to the immune response were modulated, causing the possible suppression of such a system.…”
Section: Discussionmentioning
confidence: 99%